Leshy’s “Wardrobe” (by Material of Perm Region Russian Mythological Texts) - I. I. Rusinova; M. A. Granova (Научный диалог)
The article deals with folk ideas about leshy’s clothes. The material included mythological texts from the archives of the Perm State National Research University and folklore and ethnographic collections of the Perm region. The authors proceed from the position that clothing within the traditional culture is perceived as a semiotic system that provides a variety of information about a person: indicates gender, age, family status. The paper shows that the interpretation of clothing as a cultural code is projected on the inhuman, demonic world. It is proved that leshy’s clothing is also semiotically significant: firstly, it helps to emphasize the sex of the character and some of “social” characteristics (for example, “married” female leshy wears a handkerchief), and secondly, it marks the character’s belonging to the demonic world (at the same time certain items of clothing (sheepskin coat, coats in summer, elements of a military wardrobe, high hat), the color of suit (red, black or white), as well as the lack of necessary items of clothing, for example shoes can be considered as a sign of the “inhuman” nature of leshy. Particular attention is paid to the nominative combinations that describe leshy, which include the names of garments. The analysis shows that the elements of such combinations are usually the designations of such items of clothing, which are “standard” for men’s and women’s clothing. It is established that on the territory of the Perm region there is a tendency to “modernization” of the “wardrobe” minimum of leshy.